Faktor- Faktor Penyebab Yang Menyebabkan Perilaku Tindak Pidana Korupsi Di Kalangan Pegawai Negeri - Nadya Shahnaz Gabriella; Akbar Ramadhan Gumas; Ardinia Awanis Shabrina; Febrianita Aisyah Putri (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
Corruption originates from the Latin word corruptio, which was used by Aristotle in his book degeneratio et corruptione It means change or deterioration and has no connection to power or money . Corruption offenses fall under the category of special criminal acts, thus requiring specific measures to eradicate them Indonesian positive law regulates the eradication of corruption offenses in Law Number 31 of 1999 as amended by Law Number 20 of 2001 concerning the Eradication of Corruption Offenses. Corruption is an extraordinary crime; its impact can harm democratic values, morality, national finances, and violate social and economic rights of the community It also poses a threat to the aspirations towards a better society. The factors that cause corruption are as follows: (1) Individual behavior, (2) Political factors, (3) Economic factors, (4) Legal factors, (5) Social factors This study aims to understand and provide information about corruption, types of corruption, and the factors that cause corruption in general.